2011
DOI: 10.1152/ajpheart.01120.2010
|View full text |Cite
|
Sign up to set email alerts
|

Is arterial wall-strain stiffening an additional process responsible for atherosclerosis in coronary bifurcations?: an in vivo study based on dynamic CT and MRI

Abstract: Coronary bifurcations represent specific regions of the arterial tree that are susceptible to atherosclerotic lesions. While the effects of vessel compliance, curvature, pulsatile blood flow, and cardiac motion on coronary endothelial shear stress have been widely explored, the effects of myocardial contraction on arterial wall stress/strain (WS/S) and vessel stiffness distributions remain unclear. Local increase of vessel stiffness resulting from wall-strain stiffening phenomenon (a local process due to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
(47 reference statements)
1
34
0
Order By: Relevance
“…Ohayon et al (2011) also included heart contraction in their multi-patient coronary plaque study using 3D structural models based on in vivo CT (for morphology) and MRI (for ventricle contraction). Data from eight patients were used in their study.…”
Section: In Vivo Image-based Fsi Models For Atherosclerotic Vulnermentioning
confidence: 99%
See 1 more Smart Citation
“…Ohayon et al (2011) also included heart contraction in their multi-patient coronary plaque study using 3D structural models based on in vivo CT (for morphology) and MRI (for ventricle contraction). Data from eight patients were used in their study.…”
Section: In Vivo Image-based Fsi Models For Atherosclerotic Vulnermentioning
confidence: 99%
“…The mechanisms causing plaque rupture and subsequent clinical events are not fully understood (Fuster, 1998; Fuster et al, 1990; Naghavi et al, 2003a, 2003b). Considerable progress has been made in recent years in medical imaging (Yuan et al, 2001a, 2001b; Underhill, et al, 2010), histopathological analysis (Stary et al, 1992, 1994, 1995; Virmani et al, 2000, 2006), biomechanical plaque material properties (Finet et al, 2004; Le Floc'h et al, 2012; Baldewsing et al, 2008), mechanical stress risk factors (Richardson et al, 1989; Arroyo and Lee, 1999; Ohayon et al, 2011; Loree et al, 1992). and computational models (Tang, 2006; Friedman et al, 2010) for better understanding of plaque progression, rupture and to develop possible better patient screening and plaque assessment schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that severe stenosis may inhibit wall motion. Ohayon et al [33] quantified the WSS and the stiffness in coronary bifurcations and investigated the correlations with atheroma plaque sites.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover Ding et al [37] used medical imaging technique to study the arterial motion without considering the compliance itself. In a previous study [38] we analyzed the coronary wall stiffness of 8 patients trying to find correlation with the atheromatous plaque locations, neglecting the contribution of the blood flow. The aim of this work is to evaluate how the wall compliance can affect the blood flow pattern and the WSS in a human LCA using comparing FSI and CFD analysis.…”
Section: Introductionmentioning
confidence: 99%